Analisa Tindak Tutur Dalam Tuturan Lara Pangkon Pada Upacara Temu Manten Masyarakat Kec. Ngantang - Trisnian Ifianti; Enis Fitriani (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
This study analyses Lara Pangkon's utterances at the ceremony of temu manten in Kec. Ngantang, in order to know the forms of speech acts, explain their meaning and how they are conveyed. In this research, the method used was descriptive qualitative research method, with the data source of this research is the utterances in Lara Pangkon as the main data source from and documentation books as additional data sources. In the end, this research shows that each form of speech delivered contains meanings and symbols that contain speech acts. After being studied, it can be concluded that from the 2 (two) parts of Lara Pangkon's possession, the speeches presented by both Pamasrah and Panampi contained 3 (three) expressive speech acts, 3 (three) directive speech acts, 3 (three) assertive speech acts and 2 (two) clear and commissive speech acts that can be conveyed briefly and straightforwardly.